1994
DOI: 10.1016/0304-3959(94)90146-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphine insensitive allodynia is produced by intrathecal strychnine in the lightly anesthetized rat

Abstract: The acute blockade of spinal glycinergic inhibition with intrathecal strychnine (i.t. STR; a glycine antagonist) in rats induces a change in somatosensory processing which is very similar to the sensory dysesthesia of clinical neural injury pain. In the present study, the effects of i.t. STR were examined in urethane-anesthetized rats. Noxious paw pinch (PP) or tail immersion (TI) in 55 degree C water evoked a pronounced pressor response, increased heart rate (HR) and desynchronized the electroencephalogram; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 35 publications
3
39
0
Order By: Relevance
“…The present results are also consistent with previous reports on the failure of morphine given at the segmental level, at doses close to the one we used, to block dynamic mechanical allodynia induced by glycine disinhibition (Yaksh, 1989;Sherman and Loomis, 1994;Lee et al, 1995), an observation that we now extend by showing that systemic morphine did not modify dorsal horn touch-evoked Fos expression and ERK phosphorylation. The subcutaneous dose of morphine we used (4 mg ⅐ kg Ϫ1 ) has been shown to reduce noxious stimulus-induced Fos expression in the spinal and medullary dorsal horns consistently (Presley et al, 1990;Nozaki et al, 1992;Nojima et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present results are also consistent with previous reports on the failure of morphine given at the segmental level, at doses close to the one we used, to block dynamic mechanical allodynia induced by glycine disinhibition (Yaksh, 1989;Sherman and Loomis, 1994;Lee et al, 1995), an observation that we now extend by showing that systemic morphine did not modify dorsal horn touch-evoked Fos expression and ERK phosphorylation. The subcutaneous dose of morphine we used (4 mg ⅐ kg Ϫ1 ) has been shown to reduce noxious stimulus-induced Fos expression in the spinal and medullary dorsal horns consistently (Presley et al, 1990;Nozaki et al, 1992;Nojima et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…It also involves alterations in central processing of sensory information by dorsal horn neurons (Woolf and Salter, 2006), including disinhibition through reduced inhibitory transmitter synthesis and/or release (Castro-Lopes et al, 1993;Wiesenfeld-Hallin et al, 1997), loss of inhibitory interneurons (Moore et al, 2002), block of inhibitory receptors (Ahmadi et al, 2002;Harvey et al, 2004), shift in anion gradient (Coull et al, 2005) or altered descending inhibitory modulation from the brain (Vanegas and Schaible, 2004). Glycine inhibitory dysfunction has successfully been used as a model of allodynia (Beyer et al, 1985;Yaksh, 1989;Sherman and Loomis, 1994). We recently found that glycine inhibitory dysfunction gates tactile input to superficial dorsal horn nociceptive specific neurons through protein kinase C gamma (PKC␥)-dependent activation of a local, excitatory, NMDA receptor-dependent, dorsal horn circuit (Miraucourt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Higher doses of strychnine (>10.0 μg) may cause seizure. Consistent with previous studies (13,17,41,42), intrathecal strychnine induced marked mechanical allodynia in a dose-dependent manner ( Figure 7E). However, only the highest subconvulsive dose of strychnine (10 μg) induced thermal hyperalgesia ( Figure 7F).…”
Section: Activation Of Low-threshold Aβ Fibers Evokes Ap Output Of Nosupporting
confidence: 92%
“…Thus, touch is processed as pain, thereby providing a rational explanation for the generation of allodynia. This idea is supported by the observation that impediment of inhibitory transmission in the spinal cord with bicuculline and/or strychnine produces allodynia and hyperalgesia in uninjured animals (Yaksh, 1989;Sherman and Loomis, 1994;Loomis et al, 2001).…”
Section: Altered Sensory Processing and Generation Of Allodyniamentioning
confidence: 93%
“…Some of the anticonvulsant agents used in pain management are thought to act, at least in part, by augmentation of GABA function (Table 1). Given the established role of GABAergic and glycinergic dysfunction in the etiology of allodynia (Yaksh, 1989;Sherman and Loomis, 1994;Loomis et al, 2001), restoration of this function represents an attractive therapeutic approach (Zeilhofer et al, 2012a. Augmentation of glycinergic function may be achieved by pharmacological manipulation of the glial and neuronal glycine transporters GlyT1 and GlyT2 or direct stimulation of glycine receptors (Zeilhofer et al, 2017).…”
Section: Altered Sensory Processing and Generation Of Allodyniamentioning
confidence: 99%